IPv6 Address Prefixes Reserved for Documentation - Moreiras, Antonio; Cordeiro, Edwin; Santos, Rodrigo; Servin, Arturo; Acosta, Alejandro (Anais do Workshop Pré-IETF (WPIETF), 2014)
RFC3849 speciﬁed an IPv6 preﬁx to be used in documentation, in order to reduce the likelihood of conﬂict and confusion when relating examples of deployed systems. This preﬁx was reserved to be used in examples in RFCs, books, documentation, and the like. It became widely accepted and used. Although the IPv6 documentation preﬁx proved to be very useful, a /32 preﬁx is not enough to be used to document some kinds of IPv6 deployments, such as large ISP deployments, transition techniques, and other useful examples that require longer preﬁxes. This document deﬁnes the allocation of a new global unicast (GUA) block and a new unique local (ULA) block, to expand the range of documentation blocks. It also updates RFC3849.